Dal latino iam agli esiti nelle lingue romanze: verso una configurazione pragmatica complessiva* - Bazzanella, Carla; Bosco, Cristina; Calaresu, Emilia; Garcea, Alessandro; Radulescu, Anda; Guil, Pura (Cuadernos de Filología Italiana, 2006)
The aim of this paper is to analyse a pragmatic marker from a pragmatic perspective, which is based both on the ‘global configuration’ of the relevant features and a prototype model. We will follow the diachronic development from Latin iam to its derivative forms in Romance languages, where the original values subsist, are reduced or augmented. The values shown in the fields of temporality (along the axes of past, present and future), aspectuality (particularly with regard to phasal features which characterise both iam and its Romance derivatives forms) and modality (with regard to different degrees of ‘expectation/sharing/presuppositionality and ‘emphasis/strengthening’ coming from the speaker’s commitment) are already present in Latin; only Rumanian testifies to the temporal value; Sardinian, Spanish, Portuguese display many modal features; Italian and French lie in an intermediate situation (even though not identical), where temporal and aspectual features are represented with a reduced presence of modal ones.